4A zeolite, preparation method thereof and PVC (polyvinyl chloride)

By performing the gel-forming reaction between aluminum source and silicon source at a specific temperature and crystallizing it, the problem of high moisture content of 4A zeolite is solved, and the preparation of low-moisture products is achieved, meeting the needs of the PVC industry.

CN119637895APending Publication Date: 2025-03-18CHALCO SHANDONG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814881.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

How to reduce the moisture of 4A zeolite, especially in high moisture environments, especially in winter, the problem is that it is difficult to reduce moisture.

Method used

By performing a gel-forming reaction of the aluminum source with a second temperature and a silicon source with a third temperature at the first temperature, the bonding strength of the gel-forming reaction product is adjusted to obtain a sodium aluminosilicate gel slurry and crystallized to obtain a 4A zeolite. This method improves the activity of ions in the skeleton and reduces the binding force of the skeleton to water molecules by coordinating temperature regulation.

Benefits of technology

The preparation of low-moisture products (moisture <7%) of 4A zeolites was achieved, which improved the drying efficiency and met the PVC industry's demand for low-moisture zeolites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637895A_ABST
    Figure CN119637895A_ABST
Patent Text Reader

Abstract

The invention relates to 4A zeolite, a preparation method thereof and PVC, and belongs to the technical field of zeolite preparation. The method comprises the following steps: at a first temperature, carrying out a gel forming reaction on an aluminum source with a second temperature and a silicon source with a third temperature to reduce the bonding strength of a product of the gel forming reaction so as to obtain sodium aluminosilicate gel slurry; and crystallizing the sodium aluminosilicate gel slurry to obtain the 4A zeolite. At a first temperature, an aluminum source with a second temperature and a silicon source with a third temperature are subjected to a gel forming reaction, an aluminum-oxygen tetrahedron AlO4 and a silicon-oxygen tetrahedron SiO4 of the aluminum source are combined to form a sodium aluminosilicate skeleton structure, and the first temperature, the second temperature and the third temperature synergistically improve the activity of ions in the skeleton. Therefore, the bonding strength between ions of a product of the gel forming reaction is reduced, and the binding force of a skeleton to water molecules is reduced. The 4A zeolite product prepared by the invention realizes moisture lt; 7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of zeolite preparation, and in particular to a 4A zeolite and a preparation method thereof, and PVC. Background Art

[0002] 4A zeolite belongs to the cubic crystal system, with a pore size of about 0.4nm. The basic structural unit of 4A zeolite is a three-dimensional framework structure formed by silicon-oxygen tetrahedron SiO4 and aluminum-oxygen tetrahedron AlO4 connected by shared oxygen atoms. In 4A zeolite, each aluminum-oxygen tetrahedron carries a negative charge. In order to maintain electrical neutrality, there are exchangeable cations outside the framework, usually sodium ions.

[0003] PVC-specific zeolite is a high-end series product of 4A zeolite. As a heat stabilizer, PVC-specific zeolite is widely used in the PVC plastic industry. It can neutralize and adsorb the free toxic and harmful gas hydrogen chloride produced during the PVC molding process, and prevent PVC from aging. It is a green, environmentally friendly and efficient heat stabilizer. However, the high moisture content of PVC-specific zeolite affects the product quality of downstream customers and the high-quality development of enterprises, especially in winter, when it is difficult to reduce the moisture content of PVC-specific zeolite. Summary of the invention

[0004] The present application provides a 4A zeolite and a preparation method thereof, and PVC to solve the following technical problem: how to reduce the moisture content of 4A zeolite.

[0005] In a first aspect, the present application provides a method for preparing 4A zeolite, the method comprising:

[0006] At the first temperature, an aluminum source having a second temperature and a silicon source having a third temperature are subjected to a gelling reaction to reduce the bonding strength of a product of the gelling reaction to obtain a sodium aluminosilicate gel slurry;

[0007] The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite.

[0008] Optionally, the first temperature is 48°C to 52°C.

[0009] Optionally, the second temperature is 48°C to 50°C.

[0010] Optionally, the third temperature is 46°C to 48°C.

[0011] Optionally, the temperature difference between the second temperature and the third temperature is <4°C.

[0012] Optionally, the volume ratio of the aluminum source to the silicon source is (4.8-5.1):1.

[0013] Optionally, the crystallization temperature is 75°C to 78°C.

[0014] Optionally, the aluminum source meets the following indicators:

[0015] The weight of Al2O3 is 48g / L to 50g / L, Nk is 92g / L to 95g / L, ak is 3.10 to 3.15; and / or,

[0016] The silicon source meets the following indicators: the weight of SiO2 is 26% to 27%, and the weight of Na2O is 8% to 9%.

[0017] In a second aspect, the present application provides a 4A zeolite, wherein the 4A zeolite is prepared by any method described in the first aspect.

[0018] In a third aspect, the present application provides a PVC, wherein the raw material of the PVC includes the 4A zeolite described in any one of the second aspects.

[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0020] The preparation method of the 4A zeolite provided in the embodiment of the present application comprises: at a first temperature, an aluminum source having a second temperature and a silicon source having a third temperature are subjected to a gelling reaction to regulate the bonding strength of the product of the gelling reaction to obtain a sodium aluminosilicate gel slurry; the sodium aluminosilicate gel slurry is crystallized to obtain a 4A zeolite. At a first temperature, an aluminum source having a second temperature and a silicon source having a third temperature are subjected to a gelling reaction, and the aluminum oxide tetrahedron AlO4 and the silicon oxide tetrahedron SiO4 of the aluminum source are combined to form a sodium aluminosilicate skeleton structure, and the first temperature, the second temperature, and the third temperature synergistically increase the activity of ions in the skeleton, thereby reducing the bonding strength between ions of the product of the gelling reaction, thereby reducing the binding force of the skeleton on water molecules; finally, the sodium aluminosilicate gel slurry is crystallized to obtain a 4A zeolite. Therefore, the skeleton of the 4A zeolite has a low binding force on water molecules, and a 4A zeolite product with a moisture content of <7% can be obtained after subsequent drying. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0023] Figure 1A schematic flow chart of a method for preparing 4A zeolite provided in an embodiment of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0025] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0026] In the present application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: the existence of A alone, the existence of A and B at the same time, and the existence of B alone. Among them, A and B can be singular or plural. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula according to the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one by one to the proportional numbers in the proportional formula according to the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0028] In a first aspect, the present application provides a method for preparing 4A zeolite. Figure 1 A schematic diagram of a method for preparing 4A zeolite provided in the examples of the present application; see Figure 1 , the method comprising:

[0029] S1, at a first temperature, subjecting an aluminum source having a second temperature and a silicon source having a third temperature to a gelling reaction to reduce the bonding strength of a product of the gelling reaction, thereby obtaining a sodium aluminosilicate gel slurry;

[0030] In some embodiments, the first temperature is 48°C to 52°C.

[0031] In some embodiments, the second temperature is 48°C to 50°C.

[0032] In some embodiments, the third temperature is 48°C to 52°C.

[0033] In some embodiments, the temperature difference between the second temperature and the third temperature is <4°C.

[0034] In the present application embodiment, the fundamental reason for the increase in moisture content of 4A zeolite is that the framework formed by the combination of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron has an enhanced binding force on water molecules, and the difficulty of water molecules escaping from the binding during the drying process increases, or the water molecules need more kinetic energy to escape. Therefore, the problem of reducing the moisture content of 4A zeolite is essentially to solve how to reduce the binding force of the framework on water molecules. At a first temperature, an aluminum source with a second temperature and a silicon source with a third temperature are subjected to a gelling reaction, and the aluminum-oxygen tetrahedron AlO4 and silicon-oxygen tetrahedron SiO4 of the aluminum source are combined to form a sodium aluminosilicate framework structure, and the first temperature, the second temperature, and the third temperature synergistically increase the activity of ions in the framework, thereby reducing the inter-ionic bonding strength of the product of the gelling reaction (bonding strength refers to the size of the binding force of the chemical bond between two atoms or atomic groups), thereby reducing the binding force of the framework on water molecules.

[0035] The first temperature can be 48°C to 52°C, which increases the ion activity in the aluminum source and reduces the bonding strength of the skeleton formed by the silicon-oxygen tetrahedron and the aluminum-oxygen tetrahedron, thereby reducing the binding force of the skeleton on water molecules; and can stabilize the properties of the products of the gelation reaction. For the formation process of sodium aluminosilicate gel, the appropriate temperature is conducive to the uniform mixing and orderly polymerization between the raw material molecules, and the viscosity of the formed gel is moderate. If the first temperature is higher than 52°C, the bonding inside the gel may be formed too quickly and irregularly, resulting in unstable properties of the products of the gelation reaction; if the first temperature is lower than 48°C, the gelation process may become slow, resulting in the generated gel having a loose structure or incomplete polymerization, which is difficult to arrange in order according to the crystal structure of 4A zeolite in the subsequent process, resulting in difficulty in gel decomposition and difficulty in smooth conversion into 4A zeolite crystals. Exemplarily, the first temperature can be 48°C, 49°C, 50°C, 51°C, 52°C, etc.

[0036] The second temperature can be 48°C to 50°C, which increases the ion activity in the aluminum source and reduces the bonding strength of the framework formed by the silicon-oxygen tetrahedron and the aluminum-oxygen tetrahedron, thereby reducing the binding force of the framework on water molecules; and is conducive to regulating the gelling temperature, so that the properties of the product of the gelling reaction are stable. Exemplarily, the second temperature can be 48°C, 48.5°C, 49°C, 49.5°C, 50°C, etc.

[0037] The third temperature can be 46°C to 48°C, which increases the ion activity in the silicon source and reduces the bonding strength of the framework formed by silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons, thereby reducing the binding force of the framework on water molecules; and can make the viscosity and solubility of the aluminum source better, which is conducive to the gelation reaction and stabilizes the properties of the product of the gelation reaction. Exemplarily, the third temperature can be 46°C, 46.5°C, 47°C, 47.5°C, 48°C, etc.

[0038] The temperature difference between the second temperature and the third temperature can be <4°C, which reduces the temperature difference between the sodium aluminate solution and the sodium carbonate solution, thereby regulating the temperature of the gelling reaction, reducing the bonding strength of the skeleton formed by the silicon-oxygen tetrahedron and the aluminum-oxygen tetrahedron, thereby reducing the binding force of the skeleton on water molecules, and the temperature of the aluminum source and the silicon source are similar, which is conducive to the decomposition of the gel in the subsequent crystallization to form 4A zeolite crystals. If the temperature difference between the second temperature and the third temperature is higher than 4°C, the generated gel may have a loose structure or incomplete polymerization, and it is difficult to arrange in order according to the crystal structure of the 4A zeolite in the subsequent process, which makes it difficult to decompose the gel and convert it into 4A zeolite crystals smoothly. Exemplarily, the temperature difference between the second temperature and the third temperature can be 3°C, 2°C, 1°C, 0°C, etc. In addition, for the aluminum source and the silicon source, all methods that can increase the temperature, such as steam and electric heating, can be used.

[0039] In some embodiments, the volume ratio of the aluminum source to the silicon source is (4.8-5.1):1.

[0040] In the embodiment of the present application, the volume ratio of the aluminum source to the silicon source can be (4.8-5.1):1. Regulating the volume ratio of the aluminum source to the silicon source is conducive to stabilizing the synthetic ratio of 4A zeolite and avoiding the formation of impurities. Exemplarily, the volume ratio of the aluminum source to the silicon source can be 4.8:1, 4.9:1, 5.0:1, 5.1:1, etc.

[0041] In some embodiments, the aluminum source meets the following criteria:

[0042] The weight of Al2O3 is 48g / L to 50g / L, Nk is 92g / L to 95g / L, ak is 3.10 to 3.15; and / or,

[0043] The silicon source meets the following indicators: the weight of SiO2 is 26% to 27%, and the weight of Na2O is 8% to 9%.

[0044] In the embodiment of the present application, the aluminum source meets the following indicators: the weight of Al2O3 can be 48g / L-50g / L, Nk (caustic soda) can be 92g / L-95g / L, and ak (caustic ratio) can be 3.10-3.15, which is conducive to the stable formation of sodium aluminosilicate gel slurry. Exemplarily, the weight of Al2O3 can be 48g / L, 49g / L, 50g / L, etc.; Nk can be 92g / L, 93g / L, 94g / L, etc.; ak can be 3.10, 3.11, 3.12, 3.13, 3.14, 3.15, etc. The silicon source meets the following indicators: the weight of SiO2 can be 26%-27%, the weight of Na2O can be 8%-9%, the viscosity and solubility are good, which is conducive to the gelation reaction. For example, the weight of SiO2 can be 26%, 26.5%, 27%, etc.; the weight of Na2O can be 8%, 8.5%, 9%, etc. Generally speaking, the aluminum source can be a sodium aluminate solution, and the silicon source can be a sodium silicate solution (sodium silicate).

[0045] S2. Crystallizing the sodium aluminosilicate gel slurry to obtain 4A zeolite.

[0046] In some embodiments, the crystallization temperature is 75°C to 78°C.

[0047] In the embodiment of the present application, during the crystallization process of the sodium aluminosilicate gel slurry, the aluminosilicate components inside it will be rearranged and combined under certain conditions. The silicon (Si) and aluminum (Al) atoms in the gel are bridged by oxygen (O) atoms to gradually form a regular skeleton structure. During crystallization, these atoms are arranged in order according to the crystal structure of 4A zeolite. The crystallization temperature can be 75°C to 78°C, which can make the crystal morphology of 4A zeolite better and the purity higher. Exemplarily, the crystallization temperature can be 75°C, 76°C, 77°C, 78°C, etc. In general, the 4A zeolite obtained by crystallization needs to be washed and dried to obtain a 4A zeolite product. Compared with the existing 4A zeolite product, the 4A zeolite can obtain a 4A zeolite product with lower moisture content under the same drying conditions, indicating that the skeleton of 4A zeolite has low binding force on water molecules, and it is easier to dry and dehydrate to obtain a 4A zeolite product with low moisture content, and the drying efficiency is high.

[0048] In summary, the preparation method of 4A zeolite provided in this application has the following advantages:

[0049] 1. Gelation reaction stage

[0050] The synergistic effect of temperature and its influence on ion activity: The first temperature: It is the ambient temperature of the entire gelation reaction. This temperature provides the basic thermodynamic conditions for the reaction between the aluminum source and the silicon source, so that the reaction can proceed smoothly. The appropriate first temperature can promote the appropriate movement speed of the aluminum source and silicon source molecules, ensuring that the two can fully contact and react. The second temperature (aluminum source temperature) and the third temperature (silicon source temperature): The aluminum source and the silicon source participate in the reaction with their respective initial temperatures. They work synergistically with the first temperature to jointly affect the activity of the ions in the system. Ionic activity is an indicator of the effective concentration of ions in the solution, and its size determines the degree of activity of the ions in the chemical reaction. Different temperature combinations will cause the ions around the aluminum oxygen tetrahedron in the aluminum source and the silicon oxygen tetrahedron in the silicon source to have different movement states and energy levels.

[0051] 2. Impact on bonding strength

[0052] After the activity of the ions in the skeleton is increased through the synergistic effect of the first temperature, the second temperature, and the third temperature, the bonding strength between the ions in the gelling reaction product (sodium aluminosilicate gel) will be reduced. Under normal circumstances, the ions in the sodium aluminosilicate skeleton structure are connected to each other by chemical bonds. When the bonding strength is high, the structure is relatively stable and tight. But here, by regulating the activity of the ions through temperature, the binding between the ions is no longer so strong. This change is the key to subsequently reducing the binding force on water molecules and facilitating crystallization.

[0053] 3. Influence on the binding force of water molecules

[0054] As the inter-ionic bonding strength decreases, the binding force of the sodium aluminosilicate gel skeleton structure on water molecules also decreases. Water molecules play an important role in the entire system. Under conventional high bonding strength and strong binding force, it is difficult for water molecules to move freely and participate in subsequent reactions. When the binding force decreases, water molecules can move more flexibly around the skeleton structure.

[0055] 4. Crystallization stage

[0056] After the gelation reaction and the adjustment of relevant conditions, the sodium aluminosilicate gel slurry enters the crystallization stage. At this time, due to the combined effects of factors such as the increase in ion activity, the decrease in bonding strength, and the reduction in the binding force on water molecules in the previous gelation reaction, the aluminum-oxygen tetrahedrons and silicon-oxygen tetrahedrons in the sodium aluminosilicate gel can be rearranged and combined in a more orderly and efficient manner in a relatively "loose" environment according to the crystal structure characteristics of 4A zeolite. The originally disordered gel structure gradually transformed into a 4A zeolite crystal structure with regular pores and specific crystal forms, and finally 4A zeolite was successfully obtained.

[0057] In a second aspect, the present application provides a 4A zeolite, wherein the 4A zeolite is prepared by any method described in the first aspect.

[0058] The 4A zeolite is realized based on the preparation method of the above-mentioned 4A zeolite. The specific steps of the preparation method of the 4A zeolite can refer to the above-mentioned embodiment. Since the 4A zeolite adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0059] In a third aspect, the present application provides a PVC, wherein the raw material of the PVC includes the 4A zeolite described in any one of the second aspects.

[0060] In the embodiment of the present application, the raw material of PVC (polyvinyl chloride) includes the above-mentioned 4A zeolite. The above-mentioned 4A zeolite has good adsorption performance and ion exchange performance, and has low moisture (moisture content <7%). The 4A zeolite adsorbs impurities and improves thermal stability, and the quality of the PVC product after adding the 4A zeolite is improved.

[0061] The PVC is realized based on the above-mentioned 4A zeolite. The specific preparation steps of the 4A zeolite can refer to the above-mentioned embodiment. Since the PVC adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.

[0062] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0063] Example 1

[0064] At a first temperature, a sodium aluminate solution having a second temperature and a sodium silicate having a third temperature are subjected to a gelling reaction to reduce the bonding strength of the product of the gelling reaction, thereby obtaining a sodium aluminosilicate gel slurry; wherein the sodium aluminate solution comprises: Al2O3: 49.1 g / L, Nk: 92.8 g / L, ak: 3.11; sodium silicate comprises: SiO2: 26.5%, Na2O: 8.5%; the first temperature is 49.7°C, the second temperature is 48.3°C, the third temperature is 47.5°C, and the temperature difference between the second temperature and the third temperature is 0.8°C; the volume ratio of the sodium aluminate solution to the sodium silicate is 5:1;

[0065] The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite; wherein the crystallization temperature is 77° C. and the crystallization time is 3 hours;

[0066] The 4A zeolite is washed and dried in sequence to obtain a 4A zeolite product; wherein the drying temperature is 105° C. and the drying time is 3 hours.

[0067] Example 2

[0068] At a first temperature, a sodium aluminate solution having a second temperature and a sodium silicate having a third temperature are subjected to a gelling reaction to reduce the bonding strength of the product of the gelling reaction, thereby obtaining a sodium aluminosilicate gel slurry; wherein the sodium aluminate solution comprises: Al2O3: 49.8 g / L, Nk: 94.5 g / L, ak: 3.12; sodium silicate comprises: SiO2: 26.8%, Na2O: 8.8%; the first temperature is 51.5°C, the second temperature is 49.1°C, the third temperature is 47.1°C, and the temperature difference between the second temperature and the third temperature is 2.0°C; the volume ratio of the sodium aluminate solution to the sodium silicate is 5.05:1;

[0069] The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite; wherein the crystallization temperature is 76.5°C and the crystallization time is 3 hours;

[0070] The 4A zeolite is washed and dried in sequence to obtain a 4A zeolite product; wherein the drying temperature is 105° C. and the drying time is 3 hours.

[0071] Example 3

[0072] At a first temperature, a sodium aluminate solution having a second temperature and a sodium silicate having a third temperature are subjected to a gelling reaction to reduce the bonding strength of the product of the gelling reaction, thereby obtaining a sodium aluminosilicate gel slurry; wherein the sodium aluminate solution comprises: Al2O3: 48.5 g / L, Nk: 92.6 g / L, ak: 3.14; sodium silicate comprises: SiO2: 26.6%, Na2O: 8.3%; the first temperature is 48.9°C, the second temperature is 47.5°C, the third temperature is 46.5°C, and the temperature difference between the second temperature and the third temperature is 1.0°C; the volume ratio of the sodium aluminate solution to the sodium silicate is 4.95:1;

[0073] The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite; wherein the crystallization temperature is 77.5°C and the crystallization time is 3 hours;

[0074] The 4A zeolite is washed and dried in sequence to obtain a 4A zeolite product; wherein the drying temperature is 105° C. and the drying time is 3 hours.

[0075] Comparative Example 1

[0076] At a first temperature, a sodium aluminate solution having a second temperature and a sodium silicate having a third temperature are subjected to a gelling reaction to reduce the bonding strength of the product of the gelling reaction, thereby obtaining a sodium aluminosilicate gel slurry; wherein the sodium aluminate solution comprises: Al2O3: 48.5 g / L, Nk: 92.6 g / L, ak: 3.15; sodium silicate comprises: SiO2: 26.5%, Na2O: 8.5%; the first temperature is 42°C, the second temperature is 28°C, the third temperature is 38°C, and the temperature difference between the second temperature and the third temperature is 10°C; the volume ratio of the sodium aluminate solution to the sodium silicate is 5:1;

[0077] The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite; wherein the crystallization temperature is 77° C. and the crystallization time is 3 hours;

[0078] The 4A zeolite is washed and dried in sequence to obtain a 4A zeolite product; wherein the drying temperature is 105° C. and the drying time is 3 hours.

[0079] The 4A zeolite prepared in Examples 1 to 3 and Comparative Example 1 was tested for moisture content. Please see Table 1 for the test results.

[0080] Table 1 Moisture content of 4A zeolite products

[0081] Serial number Moisture% Example 1 6.8 Example 2 6.9 Example 3 6.8 Comparative Example 1 8.1

[0082] It can be seen from Table 1 that the framework of the 4A zeolite prepared in Examples 1 to 3 has a weaker binding force on water molecules, so that under the same drying parameters, the moisture content of the 4A zeolite product is low, while the moisture content of the 4A zeolite product of Comparative Example 1 is relatively high.

[0083] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0084] (1) The 4A zeolite preparation process provided in the embodiments of the present application is simple and easy to operate, and the produced 4A zeolite can meet the needs of the PVC industry;

[0085] (2) The 4A zeolite preparation process provided in the embodiment of the present application reduces the moisture content of the 4A zeolite product while ensuring that the product performance remains unchanged;

[0086] (3) The method of increasing the temperature in the 4A zeolite preparation process provided in the embodiment of the present application is not limited as long as the required requirements can be met. Therefore, a heat exchange method can be adopted to reduce costs.

[0087] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing 4A zeolite, the method comprising: At the first temperature, an aluminum source having a second temperature and a silicon source having a third temperature are subjected to a gelling reaction to reduce the bonding strength of a product of the gelling reaction to obtain a sodium aluminosilicate gel slurry; The sodium aluminosilicate gel slurry is crystallized to obtain 4A zeolite.

2. The method according to claim 1, characterized in that The first temperature is 48°C to 52°C.

3. The method according to claim 1, characterized in that The second temperature is 48°C to 50°C.

4. The method according to claim 1, characterized in that The third temperature is 46°C to 48°C.

5. The method according to claim 1, 3 or 4, characterized in that: The temperature difference between the second temperature and the third temperature is <4°C.

6. The method according to claim 1, characterized in that The volume ratio of the aluminum source to the silicon source is (4.8-5.1):

1.

7. The method according to claim 1, characterized in that The crystallization temperature is 75°C to 78°C.

8. The method according to claim 1, characterized in that: The aluminum source meets the following indicators: The weight of Al2O3 is 48g / L to 50g / L, Nk is 92g / L to 95g / L, ak is 3.10 to 3.15; and / or, The silicon source meets the following indicators: the weight of SiO2 is 26% to 27%, and the weight of Na2O is 8% to 9%.

9. A 4A zeolite, prepared by the method according to any one of claims 1 to 8.

10. A PVC, wherein the raw material of the PVC comprises the 4A zeolite according to claim 9.